Study of Contact Time and Media Thickness on Rainwater Harvesting Technology Filtration at Tidar University - Fairuz, Agredetya Nada; Darajat, Achmad Rafi'ud; Amin, Muhammad (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2023)
Rainwater harvesting as an alternative raw water source can reduce water runoff. However, rainwater has been in contact with various pollutants in the air. In testing in Building 3, Faculty of Engineering, Tidar University, rainwater contained levels of E. Coli 8 CFU/100ml and Coliform 69 CFU/100ml which exceeded the quality standard of the Minister of Health Regulation No. 32 of 2017. This study aims to see the effect of media thickness and contact time on each mediA to improve rainwater quality using the Vertical Flow Roughing method. Up Flow filter flow with 3 filters containing zeolite gravel, activated carbon, and volcanic sand, with each having 3 different thickness variations, namely 60 cm, 70 cm, and 80 cm. The filter is operated for 18 minutes with sampling every 6 minutes. The results of logistic regression and log likelihood test showed that there was no significant effect on all filtration media in reducing the value of E. Coli and Coliform, but the highest efficiency occurred at 18 minutes with a thickness of 80 cm in each medium. In zeolite gravel filtration, the efficiency of reducing E. Coli and Coliform reaches 100%. In activated carbon filtration, the efficiency of E. Coli reduction was 100% and Coliform 51%. In volcanic sand filtration, the efficiency of E. Coli reduction is 100% and Coliform is 35%.